(3GdTGaj aj GdLhGH Ydi GdQSGdI GdNGQbI dGHf CHj GdbHGFd YHO GdQMef Hf efUhQs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bUQ Yf JCOjI eG jMH dg ef GdMb MeO GdMGeOjf hdG Edg EdG Gddg ZQZGekG dEfha GdLGMOjf s
(3BNQgG (B:s
(3hUMJ GdQhGjI HEf CejQ GdeDefjf bO JGH abdJ GdMeO ddg Ydi JhHJg Je GdLRA GdChd s
(3GdLRA GdChd fe fSNI CNQi hgj GdQSGdI GdJi HYK HgG GHf CHj GdbHGFd Edi GdEeGe GdePchQ ai TgQ ThGd SfI (B608s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQI s
(3hYdi MhGTjgG JYdjbGJ eajOI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis